Estudio Hidrológico Cuenca Chancay – Huaral, para ampliar la potencia de la Central Hidroeléctrica Tingo, de 1.2 MW a 8.8 MW en la Provincia de Huaral - Lima - López García, Henry David. (2014)
In order to evaluate water availability River Basin Bath (Lima, Peru) for the expansion of the electric power of the Tingo Hydroelectric born the proposed expansion, which is to capture all the water of the river Bathrooms under the current hydraulic diagram of Hydroelectric Tingo, ie expand the capacity of the hydraulic infrastructure (Intake, Sand Trap, Canal driving, forebay tank, pipe pressure, etc.), according to the design flow and the water availability subject of this survey. Of generated synthetic series, we have obtained the mean monthly flows, which will be used for the design of the elements of the Enlargement of the Tingo Hydroelectric. A consequence of the results of the current hydrological study, the value of the design flow for the expansion of the plant is 2.5 m3 / s, maintaining the existing hydraulic jump, which could generate power is 8.8 MW. Also, the value of the maximum rainfall for a return period of 50 years is 51.7 mm with a maximum flow of avenues 67.0 m3 / s is calculated, the flow will determine the height of the protective walls of the structures capture and conveyance. Under this scheme the description of the construction and / or modification of their components will be expanded